Dental management of patients taking antiplatelet, oral anticoagulant and novel anticoagulant medications - Bajkin Branislav; Mirković Siniša; Vučinić Predrag; Vučković Biljana; Marjanović Marjan (Vojnosanitetski Pregled)
nema